Covid-19-krisen hæmmer dansk vækstpotentiale - Mikkel Bess; Andreas Kuchler; Morten Werner (Danmarks Nationalbank, 2020)
– Due to the covid19-crisis, it is projected that Danish potential GDP will grow at a slower pace in the coming years. Potential GDP is reduced by 1.1 per cent in 2022 compared to Nationalbanken's forecast from before the covid19 outbreak. The downward revision reflects a decline in structural employment as well as productivity.
Keywords: 330; Bruttoinlandsprodukt; Produktionspotenzial; Coronavirus; Dänemark